Analysis of Students Ability on Countable and Uncountable Nouns in Writing Descriptive Text of MTsN 13 Agam - Ardila, Lia; Safitri, Loli; Sakti, Genta; Syafitri, Widya (Education Achievement: Journal of Science and Research, 2024)
This research was due to the problems that were found in MTsN 13 AGAM. The first some of students did not know how to differentiate the countable and uncountable nouns. The second, some of students felt reluctant to write in English. The third, some of students had limited vocabulary. Furthermore,  this research is aimed to find out how was the student’s ability on countable and uncountable nouns in writing descriptive text of MTsN 13 Agam. The researcher used quantitative research. The population in this research was MTsN 13 Agam. There were four classes for the ninth grade students in MTsN 13 Agam. the total population was 105 students from class nine of MTSN 13 Agam. The researcher used cluster random sampling in choosing the sample. The total sample of this study was 24 students. The instrument that use for this research was written test. The researcher gave the students 45 minutes time, and the researcher ordered the students to write a descriptive text. In conclusion, this research has provided valuable insights into the students' ability in using countable and uncountable nouns in writing descriptive texts. The findings showed that the students have a relatively good proficiency in this aspect. Based on the data above, it can be concluded that the majority of the students have good to excellent ability in using countable nouns where 23 students can use at least 3 countable nouns in their writing and only one of them that cannot use any countable noun. However, the same cannot be said for uncountable nouns as there are more students who scored poorly in this area where the total of 13 students got the score between 0-40 which categorized as poor. This could be due to various reasons such as lack of exposure to English as a language, limited.